1, 8-Cineole ameliorates oxygen-glucose deprivation/reoxygenation-induced ischaemic injury by reducing oxidative stress in rat cortical neuron/glia. (3rd August 2014) - Ryu, Sangwoo; Park, Hyeon; Seol, Geun Hee; Choi, In-Young
Abstract: Objectives: 1, 8-Cineole, the main monoterpene in many essential oils, has been used as an ingredient in flavourings and medicine. 1, 8-Cineole has been shown to possess pharmacological properties, including anti-oxidative, anti-inflammatory and anti-nociceptive actions. However, to date, no studies have examined the potential of 1, 8-cineole to protect against cerebral ischaemic injury. Methods: In this study, we investigated the neuroprotective effects of 1, 8-cineole against cortical neuronal/glial cell injury caused by oxygen-glucose deprivation/reoxygenation (OGD/R) in an in-vitro model of ischaemia. Key findings: 1, 8-Cineole significantly attenuated OGD/R-induced cortical cell injury, as well as reduced n -methyl-d -aspartate (NMDA)-induced cell injury. However, it did not inhibit NMDA-induced cytosolic calcium overload. Nevertheless, 1, 8-cineole significantly reduced the OGD/R- and NMDA-induced overproduction of reactive oxygen species (ROS). These results indicate that 1, 8-cineole exerts neuroprotection through its anti-oxidative rather than its anti-excitotoxic, properties. The decrease in OGD/R-induced intracellular superoxide in 1, 8-cineole-treated cortical cells was associated with the upregulation of superoxide dismutase activity. Moreover, 1, 8-cineole showed direct ROS scavenging activity in an assay of oxygen radical absorbance capacity. Conclusion: Collectively, these results suggest 1, 8-cineole as a potentially effective neuroprotective and anti-oxidative candidate for the treatment of patients with ischaemic stroke.